Kurdish Children' Literature Ä°n The North - Tosun, Türkan (Humanities Journal of University of Zakho, 2018)
This study analyses the Kurdish children' literature in the North. The goal is to show works which about kurdish children's literature in the North. First, the definitions of child, childhood and children's literature have been explained. Then about history of Kurdish children's literature some informations are given. Kurdish children's literature when started and who has written for the children is also mentioned. Kurdish writers, poet and intellectuals who work for children in the North are introduced. Kurdish children' magazines and publishers that publish Kurdish children's books in the North also been the subject of this article.